2012
DOI: 10.1152/ajpcell.00294.2012
|View full text |Cite
|
Sign up to set email alerts
|

GCN-2 dependent inhibition of protein synthesis activates osmosensitive gene transcription via WNK and Ste20 kinase signaling

Abstract: Lee EC, Strange K. GCN-2 dependent inhibition of protein synthesis activates osmosensitive gene transcription via WNK and Ste20 kinase signaling. Am J Physiol Cell Physiol 303: C1269 -C1277, 2012. First published October 17, 2012; doi:10.1152/ajpcell.00294.2012.-Increased gpdh-1 transcription is required for accumulation of the organic osmolyte glycerol and survival of Caenorhabditis elegans during hypertonic stress. Our previous work has shown that regulators of gpdh-1 (rgpd) gene knockdown constitutively act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 48 publications
1
24
0
1
Order By: Relevance
“…The authors first confirmed that silencing of multiple genes previously found to repress a gpdh-1 reporter (61) reduce protein synthesis and increase expression of endogenous gpdh-1 mRNA (62). They also demonstrated that protein synthesis is reduced nearly 50%, and gpdh-1 mRNA is induced Ͼ50-fold, within an hour of transfer to hypertonic agar (Fig.…”
Section: R182 Salt and Water Homeostasis In C Eleganssupporting
confidence: 64%
See 4 more Smart Citations
“…The authors first confirmed that silencing of multiple genes previously found to repress a gpdh-1 reporter (61) reduce protein synthesis and increase expression of endogenous gpdh-1 mRNA (62). They also demonstrated that protein synthesis is reduced nearly 50%, and gpdh-1 mRNA is induced Ͼ50-fold, within an hour of transfer to hypertonic agar (Fig.…”
Section: R182 Salt and Water Homeostasis In C Eleganssupporting
confidence: 64%
“…Mechanisms used to regulate protein synthesis during hypertonic stress and the downstream signals that link protein homeostasis to osmosensitive gene expression were investigated in a recent study (62). The authors first confirmed that silencing of multiple genes previously found to repress a gpdh-1 reporter (61) reduce protein synthesis and increase expression of endogenous gpdh-1 mRNA (62).…”
Section: R182 Salt and Water Homeostasis In C Elegansmentioning
confidence: 96%
See 3 more Smart Citations